Prevention of Cap-Locking of Syrup Product by Treating the Manufacturing Process of Sugar Syrup with Citric Acid Monohydrate (Bangladesh Pharmaceutical Journal, 2016)
The aim of the study was to prevent crystallization of sucrose on the bottle neck and cap of sugar syrup containing products by treating the manufacturing process with citric acid monohydrate. Diphenhydramine HCl syrup was selected as a model product for the experiment. Sugar syrup (66% w/w sucrose) and partially inverted sugar syrup (in which 66% w/w sucrose was treated with citric acid monohydrate for partially conversion of sucrose into invert sugars) were prepared and the content of invert sugar of both the sugar syrups were determined. Sugar syrup and citric acid monohydrate treated sugar syrup (partially inverted) were considered as control and test sugar syrup, respectively which were used to manufacture the Diphenhydramine HCl syrup product. The Diphenhydramine HCl syrup product that prepared using sugar syrup was considered as control syrup product and that was prepared using citric acid monohydrate treated sugar syrup (partially inverted) was considered as the test syrup product. Then experiments were designed in such a way that both control (sugar syrup and product prepared by it) and test samples (partially inverted syrup and product prepared by it) were spread on open petridishes and also spread on the neck of filled bottle, inside of caps and the bottles, which were kept at room temperature (25 0C) for 2 weeks observation. At zero time and after two weeks, crystal growths of sucrose for each experiment were checked visually. No crystal was observed in open petridishes and bottle necks of partially inverted sugar syrup of Diphenhydramine HCl syrup prepared by using partially inverted sugar syrup, where content of invert sugars was more than 75 % w/w, but remarkable crystal growths were found in open petridishes and bottle necks of sugar syrup and Diphenhydramine HCl syrup prepared by using sugar syrup, where the content of invert sugars was less than 15 % w/w.Bangladesh Pharmaceutical Journal 19(2): 190-196, 2016